Performance of and Factors Associated With Tuberculosis Screening and Diagnosis Among People Living With HIV: Analysis of 2012-2016 Routine HIV Data in Tanzania - Werner Maokola; Werner Maokola; Bernard Ngowi; Lovetti Lawson; Michael Mahande; Jim Todd; Jim Todd; Sia E. Msuya (Frontiers Media S.A., 2020)
People Living with HIV (PLHIV) should be screened for tuberculosis (TB) at every visit to the HIV care and treatment clinic (CTC), and those with positive results on screening should undergo further diagnostic investigations. We evaluated the performance of the TB diagnosis cascade among PLHIV attending CTC between January 2012 and December 2016 in three regions of Tanzania: Dar es Salaam, Iringa, and Njombe. We used descriptive epidemiology to evaluate performance and logistic regression to determine odds ratios (OR) for factors associated with TB screening and further TB diagnosis after positive TB screening. We analyzed 169,741 PLHIV who made 2,638,876 visits to CTC between January 2012 and December 2016. We excluded 2,074 (0.80%) visits as these involved PLHIV enrolled in CTC with a prior TB disease diagnosis. Of the 2,636,802 visits, 2,524,494 (95.67%) had TB screening according to national guidelines, of which 88,028 (3.49%) had TB screening positive results. Of the 88,028 visits with a positive TB screening, 27,810 (31.59%) had no records for further TB diagnosis following positive TB screening. Of all visits with positive TB screening, 32,986 (37.50%) had a TB disease diagnosis. On multivariate logistic regression, those who visited with World Health Organization (WHO) clinical stage four (aOR = 3.61, 95% CI 3.48-3.75, P < 0.001), enrolled in health center (aOR = 1.26, 95% CI 1.24-1.29, P < 0.001), enrolled in Iringa region (aOR = 1.54, 95% CI 1.50-1.57, P < 0.001), and enrolled in 2015 (aOR = 1.20, 95% CI 1.18-1.24, P < 0.001) were more likely to have no TB screening. Visits involving those who were of the female sex (aOR = 1.14, 95% CI 1.11-1.18, P < 0.001), enrolled in Njombe region (aOR = 4.36, 95% CI 4.09-4.65, P < 0.001), and enrolled in 2016 (aOR = 2.62, 95% CI 2.49-2.77, P < 0.001) were more likely to have no further TB diagnosis after positive TB screening. The study documented high performance of TB screening for PLHIV in HIV CTCs but a low transition of presumptive TB case undergoing further investigations. Better systems are needed for ensuring presumptive TB cases are diagnosed including using more efficient diagnostic methods like Gene pert.